Simple, Safe, and Cost-Effective Technique for Resected Stomach Extraction in Laparoscopic Sleeve Gastrectomy - Serhan Derici; Koray Atila; Seymen Bora; Serkan Yener (Gastroenterology Research and Practice)
Background. Laparoscopic sleeve gastrectomy (LSG) has become a popular operation during the recent years. This procedure requires resection of 80–90% of the stomach. Extraction of gastric specimen is known to be a challenging and costly stage of the operation. In this paper, we report results of a simple and cost-effective specimen extraction technique which was applied to 137 consecutive LSG patients. Methods. Between October 2013 and October 2015, 137 laparoscopic sleeve gastrectomy surgeries were performed at Dokuz Eylul University General Surgery Department, Upper Gastrointestinal Surgery Unit. All specimens were extracted through a 15 mm trocar site without using any special device. Results. We noticed one superficial incisional surgical site infection and treated this patient with oral antibiotics. No cases of trocar site hernia were observed. Conclusion. Different techniques have been described for specimen extraction. This simple technique allows extraction of specimen safely in a short time and does not require any special device.